2018
DOI: 10.3390/app8071170
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography Measures of the Achilles Tendon: Influence of Time of Day, Leg Dominance and the Impact of an Acute 30-Minute Bout of Running

Abstract: The mechanical properties of human tendons are likely to be influenced by factors known to affect elastic structures, including patterns of loading and unloading during the day. However, the exact scale and relevance of these variables to tendon stiffness remains unclear. The aim of this study was to (1) measure Achilles tendon (AT) stiffness over the course of the day, (2) examine AT stiffness between dominant and non-dominant standing leg tendons and (3) assess the impact of previous activity on AT stiffness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…That degenerative process most likely goes along with the loss of capacity of resistance to stress, which is reflected in the decrease of the Young's modulus slope [12]. A relation of shortage of load and decrease of elastographic stiffness was shown before [52,53]. This supports the hypothesis, that a tensile load is necessary to maintain the biomechanical properties [16].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…That degenerative process most likely goes along with the loss of capacity of resistance to stress, which is reflected in the decrease of the Young's modulus slope [12]. A relation of shortage of load and decrease of elastographic stiffness was shown before [52,53]. This supports the hypothesis, that a tensile load is necessary to maintain the biomechanical properties [16].…”
Section: Discussionsupporting
confidence: 67%
“…Most likely this is due to the general reduced mobility. An increase in elastographic stiffness was shown for short-term load (already after 30 min of running) [52] and also between physically active people (six or more hours of weight-bearing exercise per week) and a normal population [53].…”
Section: Discussionmentioning
confidence: 92%
“…In our experiment, all three tendon structures behaved consistently with an increase in SWV in response to 15 s maximum voluntary isometric contraction, with statistical significance only for the patellar and the Achilles tendon. Data from the literature on the matter are sparse but support our findings in that variable modes of loading resulted in an increase in Achilles tendon SWV [ 39 , 44 , 45 ]. Contrary to these findings, the global tendon stiffness assessed by measuring force-controlled tendon elongation was reduced following isometric contractions [ 58 ] and static stretching [ 59 ] in the Achilles tendon, as well as following eccentric knee extension exercises in the patellar tendon [ 60 ].…”
Section: Discussionsupporting
confidence: 84%
“…Tendon SWV is position-dependent [ 33 , 35 , 38 ], which may explain the lower reproducibility in the case of 2D SWE. Furthermore, tendon elasticity undergoes natural fluctuations in relation to loading history [ 39 ] and hydration state [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… Intra rater same day Adequate ICC = 0.93 ICC = 0.87 + Schneebeli et al, 2016 [ 35 ] 24 bilateral Intra rater same day Adequate ICC relaxed = 0.87 ICC contracted = 0.94 + NA NA NA Payne et al, 2017 [ 32 ] 8 right Intra rater same day Intra rater different days Adequate ICC T = 0.00–0.11, L = 0.01–0.11 both foot position - Adequate CV L = 80.8%-111.5% T = 53.6—112.4% ? Shear wave elastography—velocity Aubry et al, 2013 [ 38 ] 30 bilateral Inter-rater same day Doubtful ICC L = -0.011–0.46, T-0.062–0.29 NA NA NA NA DeWall et al, 2014 [ 39 ] 10 feet side not reported Inter-rater Doubtful CV = 0.156 NA NA NA NA Fu et al, 2016 [ 40 ] 326 bilateral Inter-rater same day Adequate ICC L = 0.923, T = 0.870 + NA NA NA Payne et al, 2018 [ 47 , 48 ] …”
Section: Resultsmentioning
confidence: 99%